Kajian Linguistik Forensik dalam Penyidikan Kasus Pembunuhan Engeline - Wicaksana, Sitta Devi (Humanis; Vol 27 No 2 (2023)DO - 10.24843/JH.2023.v27.i02.p10, 2023)
This study discusses the study of forensic linguistics in the investigative stage. The purpose of this study is to provide a general understanding of the role of linguistics in legal investigations. This study uses a Forensic Linguistics approach which is supported by three theories, namely the context of the situation, the cooperation principle, and the meaning of ideology. The context of the situation in the discourse includes three dimensions, namely the field of discourse, the tenor of discourse, and mode of discourse. The field of discourse in the text discusses the details of the chronology of events in which there are a witness, suspect, and investigators as tenor in the discourse. Mode of disourse has an oral form. In the principle of cooperation, the witness and suspect violate the maxim of quantity and quality due to doubts in disclosing facts. The meaning of ideology contained in the police reports is that the final decision is determined by the police because of the ideology of power they have.